Indonesia's Role in the Israeli Occupation of Palestinian Territories: New Order Era to The Reformation - Rukmana, Lisa; Kurniawanti, Merci Robbi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research examines Indonesia's involvement in the Israeli occupation of Palestine during the New Order and Reform eras. It employs a qualitative approach, utilising a literature review to analyse the role of Indonesian diplomacy in the Israeli-Palestinian conflict. The results demonstrate that Indonesia played a significant role in resolving the conflict through diplomacy. Indonesia demonstrated a firm stance of neutrality and freedom. Indonesia prioritised diplomatic efforts over those undertaken through the use of military force. In terms of international relations, Indonesia employs a multi-track diplomatic approach towards Palestine with the objective of achieving peace. Indonesia's multi-track diplomacy towards Palestine represents a form of diplomacy conducted by Indonesia with the aim of achieving world peace. The prolonged conflict that occurred when Israel occupied the Palestinian territories attracted the attention of various parties, including countries, governments, non-governmental organisations and individuals. It is crucial to acknowledge that the Indonesian government is not the sole entity engaged in conflict resolution on a global scale. This underscores the significance of Indonesia's multilateral diplomacy as a model for other countries to emulate.